Decent work and the informal economy - Anne Trebilcock (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
The ILO was founded for social justice, a mandate expressed today in terms of decent work as a global goal, for all who work, whether in formal or informal contexts. In June 2002, the delegates to the International Labour Conference from governments, workers' and employers' organizations adopted a resolution incorporating conclusions on decent work and the informal economy. The four components of decent work – opportunities for employment and income, respect for rights at work, social protection and stronger social dialogue – form the backbone of the ILO's approach to the informal economy. These elements can also be seen through a development lens, and necessarily feature a strong gender dimension. To make the action foreseen by the ILC conclusions more easily operational in a cross-disciplinary way, the issues they address can be cast in terms of macro policy, governance, enhancement of productivity, markets and employment, social protection/addressing vulnerabilities, and representation and voice. All play key roles in poverty reduction. Moreover, recognizing the importance of measuring progress towards decent work, developments in relation to indicators are briefly described. This paper includes annexes reproducing the ILC conclusions along with two relevant resolutions adopted by the International Conference of Labour Statisticians and a list of ILO websites that address various aspects of decent work and the informal economy.
Keywords: E26; J23; J40; J80; 330; employment; governance; ILO; indicators; informal sector; representation; rights; social protection; Arbeitsbedingungen; Internationale Sozialstandards; Informeller Sektor; Arbeitsverhältnis